Implementasi Budaya Siri’ Na Pacce di Tengah Arus Kebudayaan Populer - Ahmad Hairul Alamsyah (STAI DDI Kota Makassar, 2022)
With the rapid development of technology and the easier it is to access information from outside, it has resulted in the emergence of various external cultures which have become new cultures for Indonesian society without exception the Bugis-Makassar ethnic group. The rapid flow of popular culture that touches the lives of the Bugis-Makassar people has resulted in changes in behavior in social life. South Sulawesi, which is known for its siri 'na paccenya culture, which contains the value of not embarrassing oneself and others as well, is slowly starting to erode. This occurs due to the lack of education about culture on a regular basis and also the lack of supervision and filtering of the incoming foreign cultures so that people accept the outside culture at face value. As a result, the behavior pattern of the Buginese society has started to change, from the one that used to uphold and maintain the value of siri 'na pacce, now it is gradually disappearing.